A viagem de um protestante aos vales dos rios Araguaia e Tocantins na década de 1920 - Gonçalves, José Eduardo Almeida (2022)
The missionary Protestantism that was established in Brazil, from the second half of the nineteenth century, gradually expanded throughout the country and began to be represented in the most different Brazilian population contexts. Therefore, this work, using the travel report of the Scottish Protestant missionary Archibald Macintyre to the valleys of the Araguaia and Tocantins Rivers, in 1920, aims to analyze his religious discourse, in order to understand the historical constitution of the missionary narratives about the populations of the Central Cerrado in the first half of the 20th century. For this, we use works that deal with Protestantism from Europe and North America and we seek, from the ideological and ethical assumptions of missionary Protestantism, to understand categories and concepts such as morality, civility, conduct and modernity, present in the missionary's social vision of the population groups of Northern Goiás, today the State of Tocantins. The study, supported by anthropological works, seeks to consider the social practices of the populations with which the missionary sought interaction. We observe that the missionary's narrative, when compared with studies that focus on understanding historical and anthropological aspects of backlands and indigenous groups, indicates that there was a proposal to spread elements of his religious culture among northern populations. For the missionary, the acceptance of the Protestant faith would cause changes in the social, moral, and religious behavior of the interior populations, that is, the expression of those values which are typical of European and North American Protestantism.